Case Study of Empowerment through New Media Among Underrepresented Groups: GLBT Adults Gain Dominant Voice in the First Wave of Podcasting - Kathleen P. King; Sharon R. Sanquist (Adult Education Research Conference, 2008)
The podcasting movement is frequently described as “Democratization of the Media.” This case study research about gay, lesbian, bisexual and transgender (GLBT) podcasters from late 2004 to early 2008 reveals and characterizes how podcasting has yielded results of empowerment, voice, and a new media force
Keywords: empowerment; voice; transformative learning; new media; GLBT; technology